Prevalence of preconception TORCH infections and its influential factors: evidence from over 2 million women with fertility desire in southern China - Lu Han; Rui Li; Wenxue Xiong; Yang Hu; Jiabao Wu; Xiaohua Liu; Hua Nie; Weibing Qin; Li Ling; Mingzhen Li (BMC, 2023)
Abstract Background TORCH (Toxoplasma gondii [TOX], Cytomegalovirus [CMV], Rubella virus [RV], and Herpes simplex virus [HSV]) represents pathogens known to traverse the maternal-fetal barrier and cause severe neonatal anomalies. We aimed to assess the prevalence of preconception TOX, CMV, and RV infections among women with fertility desire in southern China, and identify related risk factors. Methods Data were obtained from a population-based cross-sectional study conducted as part of the National Free Preconception Health Examination Project. Women planning to conceive within the next 6 months in Guangdong Province were enrolled between 2014 and 2019. Information on sociodemographic, gynecological, and obstetric characteristics was collected. Sera were analyzed for TOX IgG, CMV IgG, and RV IgG antibodies using an enzyme-linked immunosorbent assay. Descriptive, univariate, and multivariate logistic regression analyses were performed to assess the association between TORCH infections and related factors. Results Among 2,409,137 participants, the prevalence of IgG antibodies for TOX, CMV, and RV was 3.20% (95% CI: 3.18-3.22%), 77.67% (95% CI: 77.62-77.71%) and 76.03% (95% CI: 75.98-76.07%), respectively. Of all participants, 141,047 women (5.85%, 95% CI:5.83-5.88%) reported a history of immunization for RV. Women living in the Pearl River Delta, a more developed region, have significantly lower vaccination rates than those living in other regions. The seropositivity of TOX IgG was highest among women aged 35 years and above, with primary or lower education levels, and rural registration. Factors such as being older, having a higher educational level, and being of other ethnicities were associated with a higher prevalence of naturally acquired CMV and RV infections. Women living in the Pearl River Delta showed a higher risk of TOX, CMV, and RV infections, with aORs of 2.21, 4.45, and 1.76, respectively. A history of pregnancy, gynecological diseases, and sexually transmitted infections were potentially associated with TORCH infections, but this association varied across pathogens. Conclusion The findings of this study update the baseline of preconception TORCH infections among women with fertility desire in southern China, helping to estimate the risk of congenital infection and guide the development and implementation of effective prevention measures for preconception TORCH infections.